Sistem Pendukung Keputusan Pemilihan Siswa Berprestasi di SMA Daarul Fikri Berbasis Web Menggunakan Metode AHP. - Ega; Robby Rizky; Ervi Nurafliyan Susanti (Admin Situstika, 2023)
The problem in this study is that the selection and determination of outstanding students has become a long and complicated process because the work has been semimanual, namely using MS. Excel. Every student who will be selected as an outstanding student must be in accordance with the criteria that have been set. The criteria that have been set in this case study are the average score of report cards, extracurricular grades, attendance and attitude. Therefore, only those who fit the criteria will be selected to be outstanding students. Every year there are more and more students at SM A Daarul Fikri, causing the school to find it difficult to select outstanding students. The purpose of this study is to design a Web-Based Decision Support System for Selection of Outstanding Students at SMA Daarul Fikri Using the AHP Method and can provide information about the selection of outstanding students effectively and efficiently and can be accessed easily through a Web browser. This study uses the Analytical Hierarchy Process (AHP) Method which is one of the multi-criteria decision-making methods based on the concept of outranking using pairwise comparisons of alternatives based on appropriate criteria, and the results of this study produce a Decision Support System for the Selection of Outstanding Students at SMA Daarul Fikri Web-Based Using AHP Method.